Methodological artefacts cause counter‐intuitive evolutionary conclusions in a simulation study - Loke von Schmalensee; Mats Ittonen; Anna Brødsgaard Shoshan; Kevin T. Roberts; Isabelle Siemers; Philip Süess; Christer Wiklund; Karl Gotthard (Ecology Letters, 2024)
In their simulation study, Garcia‐Costoya et al. (2023) conclude that evolutionary constraints might aid populations facing climate change. However, we are concerned that this conclusion is largely a consequence of the simulated temperature variation being too small, and, most importantly, that uneven limitations to standing variation disadvantage unconstrained populations.

Chiridota heheva—the cosmopolitan holothurian - Elin A. Thomas; Ruoyu Liu; Diva Amon; Jon T. Copley; Adrian G. Glover; Sarah J. Helyar; Karine Olu; Helena Wiklund; Haibin Zhang; Julia D. Sigwart (Marine Biodiversity, 2020)
Chemosynthetic ecosystems have long been acknowledged as key areas of enrichment for deep-sea life, supporting hundreds of endemic species. Echinoderms are among the most common taxa inhabiting the periphery of chemosynthetic environments, and of these, chiridotid holothurians are often the most frequently observed. Yet, published records of chiridotids in these habitats are often noted only as supplemental information to larger ecological studies and several remain taxonomically unverified. This study therefore aimed to collate and review all known records attributed to Chiridota Eschscholtz, 1829, and to conduct the first phylogenetic analysis into the relationship of these chiridotid holothurians across global chemosynthetic habitats. We show that Chiridota heheva Pawson & Vance, 2004 is a globally widespread, cosmopolitan holothurian that occupies all three types of deep-sea chemosynthetic ecosystem—hydrothermal vents, cold seeps and organic falls—as an organic-enrichment opportunist. Furthermore, we hypothesise that C. heheva may be synonymous with another vent-endemic chiridotid, Chiridota hydrothermica Smirnov et al., 2000, owing to the strong morphological, ecological and biogeographical parallels between the two species, and predict that any chiridotid holothurians subsequently discovered at global reducing environments will belong to this novel species complex. This study highlights the importance of understudied, peripheral taxa, such as holothurians, to provide insights to biogeography, connectivity and speciation at insular deep-sea habitats.

Serological and genetic characterization of Flavobacterium psychrophilum isolated from farmed salmonids in Turkey - I B Saticioglu; M Duman; T Wiklund; S Altun (Journal of Fish Diseases, 2018)
Turkey was the largest rainbow trout producer of the European countries in 2016, and the reason for this production is mainly attributed to its egg and fry production. Flavobacterium psychrophilum cause the highest rates of mortality in the starting to feeding stages of the fish. In the present study, twenty‐five F. psychrophilum isolates recovered from rainbow trout, coruh trout and brook trout were analysed by RAPD ‐ PCR , ERIC ‐ PCR , REP ‐ PCR and PCR ‐ RFLP , including 16S rRNA , gyr A and gyr B gene regions and PCR ‐based serotyping method. The PCR ‐based molecular analysis showed that the isolates could not be differentiated exactly according to isolation source and geographical region. Most isolates were of type‐1 and type‐2, and some of them were of type‐0 and type‐3; in addition, one isolate showed a unique serotype. The combined analysis results showed that F. psychrophilum isolates discriminated as five different genotypes and all isolates were successfully discriminated based on host.

In vivo adherence of Flavobacterium psychrophilum to mucosal external surfaces of rainbow trout ( Oncorhynchus mykiss ) fry - A Papadopoulou; I Dalsgaard; A Lindén; T Wiklund (Journal of Fish Diseases, 2017)
The adherence of Flavobacterium psychrophilum to surfaces of epithelial tissues has been inconclusively suggested as a mechanism, which enables the bacterium to invade the host. Hence, the present study aimed to examine the adherence of the cells of two colony phenotypes, smooth and rough, of F. psychrophilum to mucosal tissues of rainbow trout fry and to test the skin mucus as a nutrient for the growth of F. psychrophilum . Fish were immersed in water containing 10 6 CFU mL −1 F. psychrophilum for each colony phenotype. Mucosal tissue samples from fins, gills, skin and eyes, and swab samples from spleen and kidney were taken and inoculated onto TYES agar plates. Colony phenotypes of F. psychrophilum were identified and number of colonies counted. The results showed that cells of both phenotypes initially (0 h) adhered to all mucosal surfaces, but only the rough cells were still present on tissues 1 h post‐immersion. Both phenotypes showed a tissue tropism with the fin tissue being the most adhered. Furthermore, skin mucus promoted the growth of both colony phenotypes. We suggest that the growth of F. psychrophilum cells in skin mucus apparently facilitates the bacterial adherence to mucosal surfaces, and the subsequent invasion into the host.

Adhesion of smooth and rough phenotypes of F lavobacterium psychrophilum to polystyrene surfaces - E Högfors‐Rönnholm; J Norrgård; T Wiklund (Journal of Fish Diseases, 2015)
Phenotypic smooth cells of the fish pathogenic bacterium F lavobacterium psychrophilum have previously been reported to be more adhesive to polystyrene surfaces than corresponding rough cells. In this study, the adhesion ability of smooth and rough cells of F . psychrophilum to polystyrene surfaces was investigated in detail with a crystal violet staining method. By treating both polystyrene surfaces with fish mucus and carbohydrates and the bacterial cells with carbohydrates, the involvement of lectins in the adhesion process was investigated. Smooth cells showed significantly higher adhesion ability to untreated polystyrene surfaces compared with corresponding rough cells and increasing water hardness had an inhibitory effect on the adhesion. Treatment of polystyrene surfaces with D ‐glucose, D ‐galactose and fish mucus increased the adhesion ability of smooth cells to polystyrene. Furthermore, treatment of the smooth cells with D ‐glucose, D ‐galactose and sialic acid decreased the adhesion ability of the cells, indicating that the adhesion is likely mediated by complementary lectins on the surface of the cells. Sodium (meta)periodate treatment of smooth cells also decreased the adhesion ability to polystyrene, suggesting that the lectins, such as the dominating sialic acid‐binding lectin, are probably localized in the extracellular polysaccharides surrounding the cells.

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Molecular taxonomy of Osedax (Annelida: Siboglinidae) in the Southern Ocean - Diva J. Amon; Helena Wiklund; Thomas G. Dahlgren; Jonathan T. Copley; Craig R. Smith; Alan J. Jamieson; Adrian G. Glover (Zoologica Scripta, 2014)
We report the discovery of three new species of Osedax in the deep Southern Ocean, expanding the diversity and geographical range of this genus of bone‐eating worms. Osedax rogersi sp. n. and Osedax crouchi sp. n. were found on a whale skeleton at 1444 m in the Kemp Caldera in the East Scotia Sea during the Chemosynthetic Ecosystems of the Southern Ocean (ChEsSo) project. The recently described species, Osedax antarcticus , found on whale bones implanted at a depth of 550–650 m off Smith Island in the Bransfield Strait, was also found inhabiting the whale skeleton in the Kemp Caldera. Osedax crouchi as well as another new species Osedax nordenskjoeldi sp. n. have also been found on the implanted whale bones off Smith Island. These two localities are approximately 1800 km apart demonstrating a wide distribution of species within the genus. We describe the three new species, O. rogersi, O. crouchi and O . nordenskjoeldi and report the second record of O. antarcticus . We also present a new phylogenetic analysis for Osedax , including data examining genetic connectivity between the Scotia Arc and the Bransfield Strait.

Inhibitory activity of Pseudomonas sp. on Flavobacterium psychrophilum, in vitro - M Ström‐Bestor; T Wiklund (Journal of Fish Diseases, 2011)
A Pseudomonas sp. isolate MSB1 efficiently inhibited the growth of Flavobacterium psychrophilum of different serotypes on agar medium. A significant difference in the inhibition was observed between isolates of the less virulent Fp T serotype compared to the Fd and Th serotypes. In broth coculture experiments, a low number of cells of MSB1 inhibited and outcompeted the F. psychrophilum cells. Also cell‐free culture supernatant of MSB1 clearly repressed the growth of F. psychrophilum . A chromoazurol S assay suggested that MSB1 produced efficient siderophores, which most probably were responsible for the iron deficiency in the supernatant. The limited growth of F. psychrophilum in the supernatant was found to be partly because of the lack of available iron, but the results also indicated that some other mechanisms were probably involved in the observed inhibition. A potential use of MSB1 as a probiotic in rainbow trout aquaculture, especially in early life stages of the fish, is suggested, but future in vivo experiments needs to be carried out to verify this suggestion. This study also indicates a low iron acquisition efficiency of F. psychrophilum , compared to other examined bacterial fish pathogens.

Immunization of rainbow trout, Oncorhynchus mykiss (Walbaum), with a low molecular mass fraction isolated from Flavobacterium psychrophilum - E Högfors; K‐R Pullinen; J Madetoja; T Wiklund (Journal of Fish Diseases, 2008)
Flavobacterium psychrophilum , the causative agent of rainbow trout fry syndrome has become a widespread fish pathogen in freshwater aquaculture worldwide. In this study, a low molecular mass fraction (P25‐33), with an approximate weight of 25–33 kDa, was identified among F. psychrophilum strains in an immunoblotting analysis with anti‐ F. psychrophilum sera. The immunogenic efficacy of the isolated and extracted P25‐33 was investigated in two intraperitoneal immunization trials with rainbow trout, Oncorhynchus mykiss (Walbaum). The first trial included immunizations using P25‐33 with Freund’s complete adjuvant (FCA) and the second trial included immunizations using P25‐33, formalin‐inactivated whole and sonicated F. psychrophilum cell preparations without FCA. In both trials, antibody titres against F. psychrophilum were analysed with an enzyme‐linked immunosorbent assay and the efficacy of the immunizations was determined by a challenge with F. psychrophilum . The P25‐33 was shown to give rise to a protective immune response in rainbow trout after immunization with FCA, but not without FCA when a low concentration of P25‐33 was used. Instead formalin‐inactivated whole and sonicated cells of F. psychrophilum were able to protect the immunized fish more effectively when immunized without FCA. The results suggest that whole or sonicated F. psychrophilum cells could be better candidates for a cost‐effective water‐based injection vaccine than the immunogenic fraction.

Flavobacterium psychrophilum associated with mortality of farmed perch, Perca fluviatilis L. - L‐G Lönnström; M L Hoffrén; T Wiklund (Journal of Fish Diseases, 2008)

Temporal dynamics and nestedness of an oceanic island bird fauna - Ermias T. Azeria; Allan Carlson; Tomas Pärt; Christer G. Wiklund (Global Ecology and Biogeography, 2006)
Aim To examine temporal variation in nestedness and whether nestedness patterns predict colonization, extinction and turnover across islands and species. Location Dahlak Archipelago, Red Sea. Method The distributions of land birds on 17 islands were recorded in two periods 30 years apart. Species and islands were reordered in the Nestedness Temperature Calculator, software for assessing degrees of nestedness in communities. The occupancy probability of each cell, i.e. species–island combinations, was calculated in the nested matrix and an extinction curve (boundary line) was specified. We tested whether historical and current nested ranks of species and islands were correlated, whether there was a relationship between occupancy probability (based on the historical data) and number of extinctions or colonizations (regression analyses) and whether the boundary line could predict extinctions and colonizations (chi‐square analyses). Results Historical and current nested ranks of islands and species were correlated but changes in occupancy patterns were common, particularly among bird species with intermediate incidence. Extinction and turnover of species were higher for small than large islands, and colonization was negatively related to isolation. As expected, colonizations were more frequent above than below the boundary line. Probability of extinction was highest at intermediate occupancy probability, giving a quadratic relationship between extinction and occupancy probability. Species turnover was related to the historical nested ranks of islands. Colonization was related negatively while extinction and occupancy turnover were related quadratically to historical nested ranks of species. Main conclusions Some patterns of the temporal dynamics agreed with expectations from nested patterns. However, the accuracy of the predictions may be confounded by regional dynamics and distributions of idiosyncratic, resource‐limited species. It is therefore necessary to combine nestedness analysis with adequate knowledge of the causal factors and ecology of targeted species to gain insight into the temporal dynamics of assemblages and for nestedness analyses to be helpful in conservation planning.

Efficacy of injection vaccines against Flavobacterium psychrophilum in rainbow trout, Oncorhynchus mykiss (Walbaum) - J Madetoja; L‐G Lönnström; C Björkblom; G Uluköy; G Bylund; C Syvertsen; K Gravningen; E‐A Norderhus; T Wiklund (Journal of Fish Diseases, 2006)
Efficacy of mineral oil‐based experimental injection vaccines against Flavobacterium psychrophilum were tested in rainbow trout, Oncorhynchus mykiss (Walbaum), under laboratory and field conditions. The vaccines consisted of formalin‐ or heat‐inactivated whole bacterium cell preparations of two different serotypes (Fd and Th) or a combination of serologically different F. psychrophilum (Fd and/or Th and/or Fp T ;Th). Specific antibody responses against the bacterium in plasma and skin mucus were evaluated post‐vaccination with enzyme‐linked immunosorbent assay. Efficacy of the vaccinations was determined by challenge trials to F. psychrophilum with the vaccinated rainbow trout. Significantly higher antibody levels in plasma were detected in vaccinated fish compared with mock‐vaccinated fish. Injection vaccination did not trigger specific antibody production in the skin mucus. Significantly higher survival of i.p. vaccinated fish compared with non‐vaccinated fish was observed during the challenge. The results suggest that mineral oil‐based injectable vaccines containing formalin‐ or heat‐inactivated virulent cells of F. psychrophilum effectively triggered specific antibody production and protected the fish against bacterial cold water disease.

Phenotypic and genotypic characterization of Flavobacterium psychrophilum from Finnish fish farms - J Madetoja; M‐L Hänninen; V Hirvelä–Koski; I Dalsgaard; T Wiklund (Journal of Fish Diseases, 2001)
Finnish isolates ( n =37) of Flavobacterium psychrophilum isolated from farmed salmonids were studied using phenotypic and genotypic characteristics. The characteristics of isolates were compared with the characteristics of Swedish and Estonian F. psychrophilum isolates and the type strain, F. psychrophilum NCIMB 1947 T . Multiple isolates from eight disease outbreaks were examined to determine differences between isolates from a single outbreak. The F. psychrophilum isolates represented a biochemically homogeneous group. However, some minor differences in biochemical and physiological characteristics were observed. Seven different antigenic patterns among Finnish isolates were detected and the results suggest a new serotype of F. psychrophilum . Using Cla Ι, Hae ΙΙΙ and Pvu ΙΙ restriction enzymes in ribotyping analyses 13 different genotypes were demonstrated and a possible relationship between serotype Fd and genotype F1 was determined. There were no significant differences between the isolates from Finland, Estonia, Sweden and the type strain of F. psychrophilum .